Graphite composite negative electrode material, preparation method thereof and lithium ion battery

By growing a metal-organic frame mesh structure and covering a soft carbon cladding layer on the surface of the graphite material, the graphite composite negative electrode material that forms a core-shell structure is solved, and the problem of improved conductivity but insufficient structural design in the prior art is solved, and the improvement of high conductivity and good cycle performance is achieved.

CN119560561AActive Publication Date: 2025-03-04MINMETALS EXPLORATION & DEVELOPMENT CO LTD

Patent Information

Application Number
CN202411856738.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-04
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, the surface modification of graphite material only covers the surface and does not extend to the carbonized layer, resulting in improved conductivity but insufficient structural design, affecting the cyclic stability and rate performance of the battery.

Method used

The graphite composite anode material using a core-shell structure forms a conductive intermediate layer by growing a metal-organic frame mesh structure on the surface of natural graphite, and covers a dense soft carbon cladding layer on the outer surface to improve the conductive properties and structural strength.

Benefits of technology

It significantly improves the conductivity and cycling performance of graphite negative electrode materials, reduces internal resistance, enhances the charging and discharging performance of lithium-ion batteries, and improves the first week of Coulomb efficiency and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560561A_ABST
    Figure CN119560561A_ABST
Patent Text Reader

Abstract

The invention provides a graphite composite negative electrode material and a preparation method thereof, and a lithium ion battery, the graphite composite negative electrode material has a core-shell structure, and comprises a graphite core, a mesh conductive intermediate layer and a surface soft carbon coating layer; the raw materials of the net-shaped conductive middle layer comprise polyhydroxy benzene and metal salt, the raw material of the graphite inner core comprises natural graphite, and the raw material of the surface soft carbon coating layer comprises high-temperature coating asphalt; the mass ratio of the natural graphite to the polyhydroxy benzene to the metal salt to the high-temperature coated asphalt is 1000: (20-80): (20-80): (20-60). According to the invention, the natural graphite negative electrode material with high first-cycle coulombic efficiency, high rate capability and excellent long cycle performance can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery electrode materials, and in particular to a graphite composite negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion secondary batteries are widely used in many fields due to their high energy density, long life, low self-discharge and environmental protection characteristics. As one of its core materials, the negative electrode material directly affects the various performances of the battery. Natural graphite is the main raw material for negative electrode materials, but it has defects such as expansion effect and anisotropy, which affect the cycle stability of the battery. To overcome these problems, the industry uses asphalt and resin coating materials mixed with spherical graphite, and carbonized them under a protective atmosphere to form an amorphous carbonized layer to cover the graphite surface. This process effectively repairs the surface defects of graphite, reduces the co-embedding phenomenon of the electrolyte, and significantly improves its electrochemical performance. The performance of the coating material and the coating layer after carbonization determines the overall performance of the natural graphite negative electrode material. By adding and plating metal elements inside or on the surface of the coating layer, the conductivity of the negative electrode material can be improved, the internal resistance can be reduced, and the charge and discharge performance of the lithium-ion battery can be enhanced.

[0003] For example, CN113394402A coats the outer layer of spherical graphite with a uniform single-layer mesh-like metallic copper. The mesh-like pores of the copper layer allow lithium ions to pass through, and copper can improve the rate performance of the material; CN113991076B forms a layer of nano-copper particles on the graphite surface by chemical plating, thereby improving the conductivity of electrons on the material surface and the migration rate of lithium ions.

[0004] It can be seen that the metal conductive particles produced by the surface modification of the existing technology only cover the surface of the graphite material and do not extend to the carbonized layer. The copper-containing conductive layer can only improve the conductivity without giving it more functions through structural design.

[0005] Therefore, providing a new type of graphite composite negative electrode material and a preparation method thereof and a lithium ion battery has become a technical problem that urgently needs to be solved in the field. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a graphite composite negative electrode material and a preparation method thereof and a lithium ion battery.

[0007] To achieve the above-mentioned purpose, the present invention provides a graphite composite negative electrode material having a core-shell structure, wherein the graphite composite negative electrode material comprises a graphite core, a mesh conductive intermediate layer and a surface soft carbon coating layer; wherein the raw material of the mesh conductive intermediate layer comprises polyhydroxybenzene and metal salt, the raw material of the graphite core comprises natural graphite, and the raw material of the surface soft carbon coating layer comprises high-temperature coated asphalt; the mass ratio of the natural graphite: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000:20-80:20-80:20-60.

[0008] The present invention creates active sites on the surface of natural graphite, grows a metal-organic framework network structure in situ under hydrothermal conditions, and after calcination, some organic components are volatilized to form a network coating layer with a certain structural strength and containing uniform conductive metal particles, and covers the outer surface with a dense soft carbon coating layer, thereby improving the conductivity of the natural graphite negative electrode material, reducing impedance, and utilizing the good network structure gaps to buffer the expansion effect of natural graphite during the cycle process, thereby improving the cycle performance of the negative electrode material.

[0009] In the above graphite composite negative electrode material, preferably, the mass ratio of natural graphite: polyhydroxybenzene: metal salt: high temperature coated asphalt is 1000: 40-60: 50-70: 45-60. In the above graphite composite negative electrode material, preferably, the monomer carbon number of the polyhydroxybenzene is 6-15, and the carbon-hydrogen ratio is 1-1.2.

[0010] In the above graphite composite negative electrode material, preferably, the polyhydroxybenzene includes hexahydroxybenzene and / or 3,3',4,4',5,5'-hexahydroxybiphenyl.

[0011] In the present invention, the network-like conductive layer in situ grown on the surface of natural graphite is based on polyhydroxybenzene as a framework. The polyhydroxybenzene selected for bridging in the present invention has abundant hydroxyl groups and high unsaturation. The hydroxyl groups can bridge and grow on the surface of natural graphite with active sites to form a porous network structure. The hydroxyl groups react with the metal acetate, and the copper particles are captured by the network structure and evenly dispersed in the network structure. Unlike other organic ligands, the highly unsaturated π bonds and appropriate carbon number of polyhydroxybenzene ensure that the network structure is not easy to collapse during the calcination process. The residual carbon and metal ions after high-temperature treatment retain the network structure, have a certain strength to absorb stress, and provide good conductivity.

[0012] In the above-mentioned graphite composite negative electrode material, preferably, the metal salt includes one or a combination of two or more of copper acetate, cobalt acetate and zinc acetate.

[0013] In the above-mentioned graphite composite negative electrode material, preferably, the softening point of the high-temperature coated asphalt is 250-300°C, more preferably 275-300°C, and the coking value is ≥70%, more preferably ≥75%.

[0014] In the above-mentioned graphite composite negative electrode material, preferably, the quinoline insoluble matter content in the high-temperature coated asphalt is ≤0.3wt%, and the ash content is ≤0.1wt%; wherein the quinoline insoluble matter content and the ash content are both calculated based on the total weight of the coated asphalt as 100%.

[0015] In the above-mentioned graphite composite negative electrode material, preferably, the median particle size D50 of the high-temperature coated asphalt is 1-6μm, more preferably 2-4μm. In the present invention, the soft carbon coating generated by carbonization of the high-temperature coated asphalt can further reduce the specific surface area of ​​the negative electrode material, avoiding the decrease in the first-week coulomb efficiency caused by the formation of too many SEI films (solid electrolyte interface films) due to the large number of holes and large specific surface area of ​​the mesh structure layer. The combination of the mesh conductive layer and the soft carbon coating layer not only improves the conductivity of the negative electrode material, provides good buffering performance, reduces internal resistance, but also forms a dense carbonized layer on the surface, isolating the electrolyte from the copper particles that promote conductivity, and avoiding escape into the electrolyte during charging and discharging.

[0016] In the above-mentioned graphite composite negative electrode material, preferably, the natural graphite is spherical graphite, the median particle size D50 is 16-18 μm, and the fixed carbon content is ≥99.95wt%; wherein the fixed carbon content is calculated based on the total weight of the natural graphite as 100%.

[0017] In the above-mentioned graphite composite negative electrode material, preferably, the tap density of the natural graphite is ≥0.96 g / cm 3 , more preferably ≥ 0.98 g / cm 3 .

[0018] In the above-mentioned graphite composite negative electrode material, preferably, the specific surface area of ​​the natural graphite is ≤6.5 cm 2 / g, more preferably ≤6.0 cm 2 / g.

[0019] The present invention also provides a method for preparing the above-mentioned graphite composite negative electrode material, which comprises: (1) Using surfactants to modify the surface of natural graphite to obtain surface-modified graphite; (2) mixing the surface-modified graphite and polyhydroxybenzene in water, then adding a metal salt to carry out a hydrothermal reaction, and carbonizing the product after the reaction is completed to obtain an intermediate product; (3) The intermediate product is mixed evenly with high-temperature coated asphalt, and then carbonized again to obtain the graphite composite negative electrode material.

[0020] The natural graphite, surfactant, polyhydroxybenzene, metal salt and high-temperature coated asphalt used in the present invention can be obtained by conventional means in the art, such as commercial purchase or acquisition.

[0021] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in step (1), the method of using a surfactant to modify the surface of natural graphite is: uniformly mixing the surfactant and water, slowly adding graphite under stirring, heating and stirring, filtering, and drying to obtain the surface-modified graphite.

[0022] In the method for preparing the above-mentioned graphite composite negative electrode material, preferably, during the modification of natural graphite, the heating and stirring temperature is 40-70°C and the time is 20-120 min; more preferably, the drying temperature does not exceed 80°C.

[0023] In the preparation method of the above-mentioned graphite composite negative electrode material, preferably, in the modification of natural graphite, the surfactant includes sodium dodecylbenzene sulfonate and / or hexadecyltrimethylammonium bromide. In the present invention, the use of surfactants can improve the wettability of graphite and water, help graphite to be better dispersed in the solution medium, and at the same time, the amphiphilic groups of the surfactants can form bonds with the graphite surface, providing active sites for the uniform growth of the metal-organic network structure.

[0024] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in the modification of natural graphite, the mass ratio of the surfactant to the natural graphite is 1-10:1000.

[0025] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in the modification of natural graphite, the mass ratio of water to natural graphite is 5-15:1.

[0026] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in step (2), the temperature of the hydrothermal reaction is 70-95° C. and the time is 20-120 min.

[0027] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in step (2), the mass ratio of water to the surface-modified graphite is 15-30:1.

[0028] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in step (2), the carbonization method is: heating to 750-950°C at a heating rate of 1-10°C / min and keeping the temperature for 1-4h.

[0029] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, in step (3), the method of re-carbonization is: heating to 1100-1350° C. at a heating rate of 1-10° C. / min and keeping the temperature for 1-6 h.

[0030] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, the two carbonizations are respectively carried out under nitrogen protection.

[0031] In the above-mentioned method for preparing the graphite composite negative electrode material, preferably, the heating and stirring in step (1) and the hydrothermal reaction process in step (2) are both carried out in a reactor with heating and stirring functions, including but not limited to a glass reactor, a polytetrafluoroethylene reactor and a stainless steel reactor.

[0032] In the preparation method of the above-mentioned graphite composite negative electrode material, preferably, the two carbonizations of steps (2) and (3) are carried out in an atmosphere furnace; preferably, step (2) also includes: naturally cooling the obtained carbonized product after carbonization, and then breaking it up and sieving it; step (3) also includes: naturally cooling the obtained carbonized product after carbonization, and then breaking it up, sieving it and demagnetizing it to obtain the graphite composite negative electrode material. The mixing process is carried out in a mixer.

[0033] According to a specific embodiment of the present invention, preferably, the method for preparing the above-mentioned graphite composite negative electrode material comprises the following steps: S1: Evenly mix the surfactant and water, slowly add natural graphite under stirring, heat and stir for a period of time, filter and dry to obtain intermediate material 1; S2: Mix polyhydroxybenzene and water, slowly add intermediate material 1 under stirring, then metal salt, heat and stir for a period of time, filter and dry to obtain intermediate material 2; S3: under the protection of an inert gas, carbonizing the intermediate material 2 to obtain an intermediate material 3; S4: Under the protection of inert gas, the intermediate material 3 and the high-temperature coated asphalt are mixed evenly to obtain the intermediate material 4; S5: Under the protection of an inert gas, carbonizing the intermediate material 4 to obtain the graphite composite negative electrode material.

[0034] In the graphite composite negative electrode material provided by the present invention, the mesh conductive intermediate layer and the surface soft carbon coating layer have the functions of repairing the surface defects of natural graphite, reducing the specific surface area, improving the conductivity of the graphite material, isolating the electrolyte and the natural graphite body, and reducing the co-embedding phenomenon of lithium ions and electrolyte molecules. At the same time, the mesh conductive coating layer with a certain structural strength provides a buffer for the expansion effect of natural graphite during lithium deintercalation, thereby improving the electrochemical properties of the natural graphite negative electrode material, such as the first cycle coulomb efficiency, rate performance and long cycle performance.

[0035] The present invention also provides a lithium ion battery, wherein the negative electrode of the lithium ion battery is prepared from the above-mentioned graphite composite negative electrode material or the graphite composite negative electrode material prepared by the preparation method of the above-mentioned graphite composite negative electrode material.

[0036] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: The present invention adopts the in-situ growth technology of metal-organic framework to grow a uniform layer of organic framework containing conductive particles on the graphite surface. Through the appropriate selection of organic ligands, with the help of the moderate carbon number, high unsaturation and rich hydroxyl structure of polyhydroxybenzene, the calcined network-like conductive layer obtains uniform conductive particle distribution and high stress absorption strength. Then, through secondary coating, the conductive layer with many holes and large specific surface area is covered with a dense carbon layer, which ensures the low specific surface area and high first-cycle coulomb efficiency of the graphite composite negative electrode material. The combination of the double-layer structure also avoids the conductive mesh buffer layer from exposing the metal conductive particles, causing the conductive particles to diffuse into the electrolyte and causing the battery safety to decrease. At the same time, the presence of the conductive layer also makes up for the shortcomings of poor conductivity of high-temperature asphalt and deviation of adhesion of the graphite matrix. Through the technical solution provided by the present invention, a natural graphite negative electrode material with high first-cycle coulomb efficiency, high rate performance and excellent long-cycle performance can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 2 of the present invention; Figure 4 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 3 of the present invention; Figure 5 A transmission electron microscope image of the graphite composite negative electrode material provided in Example 1 of the present invention; Figure 6 A transmission electron microscope image of the graphite composite negative electrode material provided in Comparative Example 1 of the present invention; Figure 7 A transmission electron microscope image of the graphite composite negative electrode material provided in Comparative Example 2 of the present invention; Figure 8 This is a transmission electron microscope image of the graphite composite negative electrode material provided in Comparative Example 3 of the present invention; Fig. 9 AC impedance spectra of negative electrode materials provided in Examples 1-6 and Comparative Examples 1-5 of the present invention; Fig.10 Cycle curves of negative electrode materials provided in Examples 1-6 and Comparative Examples 1-5 of the present invention at different rates; Fig.11 1C / 1C cycle diagram of the negative electrode materials provided in Examples 4-6 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION

[0038] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0039] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0040] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0041] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0042] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0043] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0045] The raw materials used in the embodiments of the present invention are as follows: Natural graphite is spherical graphite, which is a common commercial product with a median particle size of D50 = 16.39 μm, a fixed carbon content of 99.97 wt%, and a tap density of 1.00 g / cm 3 , with a specific surface area of ​​5.80 cm 2 / g; The high-temperature coated asphalt is a conventional commercial product with a measured softening point of 279°C, a coking value of 65.7%, a quinoline insoluble matter content of 0.16wt%, an ash content of 0.05wt%, and a median particle size D50 = 3.32μm.

[0046] Example 1 This embodiment provides a graphite composite negative electrode material, and the preparation method thereof includes the following specific steps: S1: Add surfactant hexadecyltrimethylammonium bromide into a reactor filled with deionized water at 60°C and start stirring; after the hexadecyltrimethylammonium bromide is completely dissolved, add natural graphite in small amounts and slowly, wherein the mass ratio of natural graphite: surfactant: water is 1000:1:10000; after the natural graphite is evenly dispersed in the aqueous solution and there is no powder floating or agglomerated on the surface, keep stirring at 60°C for 1h, filter to obtain a filter cake and dry it in an oven at 80°C to obtain intermediate material 1, i.e., surface-modified graphite; S2: Add hexahydroxybenzene (polyhydroxybenzene) into a reactor filled with 60°C deionized water, start stirring, and after the hexahydroxybenzene is completely dissolved, slowly add intermediate material 1 (surface-modified graphite) in small amounts, wherein the mass ratio of water to surface-modified graphite is 20:1; after the intermediate material 1 is evenly dispersed in the aqueous solution and there is no powder floating or agglomerated on the surface, slowly drip an aqueous solution of copper acetate (metal salt), then heat to 80°C, stir, and keep warm for 90 minutes, filter to obtain a filter cake, and dry it in an oven at 80°C to obtain intermediate material 2; S3: placing the intermediate material 2 in an atmosphere furnace, heating it to 850°C at a heating rate of 5°C / min under the protection of high-purity nitrogen, and keeping it at that temperature for 2 hours for carbonization. After the carbonization is completed, the obtained product is cooled naturally and then broken up to obtain the intermediate material 3; S4: The intermediate material 3 and the high-temperature coated asphalt are mixed uniformly in a high-speed cyclone mixer, and high-purity nitrogen is introduced into the mixing process for protection to obtain the intermediate material 4; S5: The intermediate material 4 is placed in an atmosphere furnace, and under the protection of high-purity nitrogen, the temperature is increased to 1150°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours for carbonization. After the carbonization is completed, the obtained product is naturally cooled, and then dispersed, sieved, and demagnetized to obtain a graphite composite negative electrode material.

[0047] Among them, the feed mass ratio of natural graphite: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000:20:20:20.

[0048] Example 2 The present embodiment provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, with the only difference that: the surfactant used in S1 is sodium dodecylbenzene sulfonate, the polyhydroxybenzene in S2 is 3,3',4,4',5,5'-hexahydroxybiphenyl, and the metal salt is a combination of cobalt acetate and zinc acetate; the mass ratio of natural graphite: polyhydroxybenzene: cobalt acetate (metal salt): zinc acetate (metal salt): high-temperature coated asphalt is 1000:80:40:40:60, and the mass ratio of natural graphite: surfactant: water in S1 is 1000:10:10000.

[0049] Example 3 The present embodiment provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that: the polyhydroxybenzene in S2 is a composition of hexahydroxybenzene and 3,3',4,4',5,5'-hexahydroxybiphenyl; the mass ratio of natural graphite: hexahydroxybenzene (polyhydroxybenzene): 3,3',4,4',5,5'-hexahydroxybiphenyl (polyhydroxybenzene): metal salt: high-temperature coated asphalt is 1000: 25:25:50:40; the mass ratio of natural graphite: surfactant: water in S1 is 1000:5:10000.

[0050] Example 4 The present embodiment provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that: the polyhydroxybenzene in S2 is a composition of hexahydroxybenzene and 3,3',4,4',5,5'-hexahydroxybiphenyl; the metal salt is a composition of cobalt acetate and zinc acetate; the mass ratio of natural graphite: hexahydroxybenzene (polyhydroxybenzene): 3,3',4,4',5,5'-hexahydroxybiphenyl (polyhydroxybenzene): cobalt acetate (metal salt): zinc acetate (metal salt): high-temperature coated asphalt is 1000: 20:20:25:25:45; the mass ratio of natural graphite: surfactant: water in S1 is 1000:5:10000.

[0051] Example 5 This embodiment provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that the mass ratio of natural graphite: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000:60:70:60; the mass ratio of natural graphite: surfactant: water in S1 is 1000:5:10000.

[0052] Example 6 The present embodiment provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that: the polyhydroxybenzene in S2 is a composition of hexahydroxybenzene and 3,3',4,4',5,5'-hexahydroxybiphenyl; the mass ratio of natural graphite: hexahydroxybenzene (polyhydroxybenzene): 3,3',4,4',5,5'-hexahydroxybiphenyl (polyhydroxybenzene): metal salt: high-temperature coated asphalt is 1000: 25:25:60:52.5; the mass ratio of natural graphite: surfactant: water in S1 is 1000:5:10000; the carbonization temperature in S5 is 1350°C, and the insulation time is 4h.

[0053] Comparative Example 1 This comparative example provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that: after obtaining the intermediate material 3, demagnetization is performed, and the surface soft carbon coating steps S4 and S5 are not performed.

[0054] Comparative Example 2 This comparative example provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that: the natural graphite is only subjected to the S4 and S5 surface soft carbon coating steps, and the S1, S2, S3 mesh conductive layer coating steps are not performed.

[0055] Comparative Example 3 This comparative example provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that polyhydroxytoluene is replaced by 10-hydroxystearic acid.

[0056] Comparative Example 4 This comparative example provides a graphite composite negative electrode material, the preparation method of which is the same as that of Example 1, except that the mass ratio of natural graphite: surfactant: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000:5:75:95:45; Comparative Example 5 This comparative example provides a graphite composite negative electrode material, and its preparation method is the same as that of Example 1, except that the mass ratio of natural graphite: surfactant: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000:5:18:22:45.

[0057] Test Example 1: In this test example, a ZEISS SUPRA55 scanning electron microscope was used to perform field emission scanning electron microscope analysis on the graphite composite negative electrode materials provided in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention under conventional test conditions. The obtained scanning electron microscope images are shown in FIG. Figure 1-Figure 4 As shown. Among them, Figure 1 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Example 1 of the present invention. Figure 2 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 1 of the present invention. Figure 3 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 2 of the present invention. Figure 4 This is a scanning electron microscope image of the graphite composite negative electrode material provided in Comparative Example 3 of the present invention. The graphite composite negative electrode materials obtained in Example 1 and Comparative Examples 1-3 are all potato-shaped, in which it can be observed that Figure 1 , Figure 3 The surface of the medium particles is relatively smooth and flat. Figure 2 , Figure 4 The surface of the particles is relatively rough and sharp.

[0058] Test Example 2: In this test example, a JEM-F200 field emission transmission electron microscope was used to perform transmission scanning electron microscope analysis on the graphite composite negative electrode materials provided in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention under conventional test conditions. The obtained scanning electron microscope images are shown in FIG. Figure 5-Figure 8 As shown. Among them, Figure 5 Transmission scanning electron microscope analysis of the graphite composite negative electrode material provided in Example 1 of the present invention. Figure 6 Transmission scanning electron microscope analysis of the graphite composite negative electrode material provided in Comparative Example 1 of the present invention. Figure 7 Transmission scanning electron microscope analysis of the graphite composite negative electrode material provided in Comparative Example 2 of the present invention. Figure 8 The graphite composite negative electrode material provided in Comparative Example 3 of the present invention is analyzed by transmission scanning electron microscope. The uniformity of the coating thickness and the density of the coating can be observed by transmission electron microscope, such as Figure 5As shown, the surface of the negative electrode particles in Example 1 presents an obvious double-layer coating structure, the inner coating layer has no obvious crystal structure, the outer coating layer has a typical soft carbon structure, a short-range irregular layered structure can be observed, the inner and outer coating layers are uniform, and the inner coating layer is slightly thicker than the outer coating layer. Figure 6 , Figure 7 As shown, only a single layer of coating can be observed on the surface of the negative electrode material particles of Comparative Example 1 and Comparative Example 2, respectively. The coating on the surface of the particles of Comparative Example 1 has no obvious crystal structure, while the coating on the surface of the particles of Comparative Example 2 has an obvious layered structure, which is a typical soft carbon coating. Figure 8 As shown, the surface of the negative electrode material particles of Comparative Example 3 also presents an obvious double-layer coating. Compared with Example 1, the inner coating layer is thicker and has poor color uniformity.

[0059] Test Example 3: In this test example, the particle size and specific surface area of ​​the negative electrode materials provided in each embodiment and the comparative example were tested using a Bettersize 2600 laser particle size analyzer and a Micromeritics TriStar II 3020 fully automatic specific surface and pore size distribution analyzer under conventional test conditions. The AC impedance spectrum of the negative electrode materials provided in each embodiment and the comparative example was tested using a CHI 660E under conventional test conditions. The obtained AC impedance spectrum is shown in FIG. Fig. 9 The obtained particle size and specific surface area data are shown in Table 1 below; This test example also tests the electrochemical properties of the negative electrode materials provided in each embodiment and comparative example, including: The natural graphite negative electrode material provided in each embodiment and each comparative example was used as the negative electrode active material, and the three were mixed evenly in a mass ratio of negative electrode active material: LA133:SuperP=94:3:3, and then coated on a copper foil current collector, and then dried, cut, and rolled to obtain a negative electrode sheet for standby use.

[0060] The negative electrode sheets obtained above were assembled into 2032 button cells and tested for the first charge capacity and the first week coulomb efficiency, wherein the counter electrode was a lithium sheet, the solute of the electrolyte was LiPF6, the solvent was a mixture of DEC, DMC and EC in a volume ratio of 1:1:1, the concentration of the solute was 1 mol / L, the diaphragm was commercially available Celgard2320, and the test was carried out on a battery tester CT300A1U, the charge and discharge voltage was 0.005-1.5V, deep discharge (0.1C-0.01C) and 0.1C charge were carried out in the first week, and the first charge capacity and the first week coulomb efficiency obtained from the test are also listed in Table 1 below.

[0061] For the rate performance and cycle performance of the negative electrode material, the mass ratio of active material: LA133: SuperP = 90:5:5 was used, and the charge and discharge were carried out at 0.3C, 0.5C, 1C, 3C, and 5C respectively to test the rate performance of the negative electrode material; the charge and discharge were carried out under 1C / 1C conditions to test the cycle performance of the negative electrode material. The other test conditions were the same as the first charge capacity and first week coulomb efficiency tests. The cycle curves at different rates are shown in the figure below. Fig.10 As shown, the capacity retention rates at different rates are listed in Table 1 below, and the obtained 500-week 1C / 1C cycle diagram is shown in Fig.11 The 1C / 1C 500-cycle capacity retention results are also listed in Table 1 below.

[0062] Table 1 Battery performance test of graphite composite negative electrode materials of embodiments and comparative examples

[0063] Note (in Table 1): The present invention tests the negative electrode material by making a button half-cell. Under normal circumstances, an improvement of 15%-20% in 1C capacity retention rate, 10%-20% in 3C capacity retention rate, and 5%-10% in 5C capacity retention rate is considered effective, and an improvement of 25%, 20%, and 10% or more, respectively, is considered significant. An improvement of 3%-5% in 1C / 1C 500-cycle capacity retention rate is considered effective, and an improvement of more than 5% in 1C / 1C 500-cycle capacity retention rate is considered significant.

[0064] From Table 1 and Figure 9-11 It can be seen that compared with the double-layer coated graphite composite negative electrode material provided in Example 1, Comparative Example 1 is only coated with a mesh conductive layer. Figure 6 It can be seen that the coating layer is in a diffuse state without obvious boundaries, and the specific surface area is increased from 2.25 to 3.48 m2 compared with Example 1. 2 / g, and the first efficiency dropped significantly to 92.74%, and the 1C / 1C 500-week capacity retention rate also dropped to 86.3%. The rate performance and internal impedance were not significantly different from those in Example 1, indicating that a single mesh copper particle conductive layer can improve the conductivity of the negative electrode material. However, due to the large number of voids and low density of the conductive coating layer, the specific surface area is much higher than that of the conductive coating layer formed by high-temperature asphalt. The excessively high specific surface area consumes more Li to form the SEI film during the first charge and discharge process. At the same time, the diffusion of copper particles into the electrolyte during the charge and discharge process also causes a decrease in the cycle performance.

[0065] Compared with the double-layer coated graphite composite negative electrode material provided in Example 1, Comparative Example 2 is only coated with a soft carbon coating layer formed by high-temperature asphalt, which is a conventional process for natural graphite negative electrode materials. Figure 7It can be seen that the coating layer is a short-range layered structure with obvious boundaries, which is a typical soft carbon structure. Since the outer coating structure is the same as that of Example 1, the specific surface area and first efficiency are also similar to those of Example 1. The difference is that after adding the inner conductive coating layer to Example 1, the internal impedance is greatly reduced, and the 1C / 3C / 5C capacity retention rates are increased by 19.4%, 18.8% and 9.7% respectively. The 1C / 1C 500-week capacity retention rate is also greatly increased from 89.1% to 94.5%. The surface mesh conductive layer structure provides better conductivity through copper particles, thereby reducing internal resistance and improving rate performance. At the same time, the buffering of the mesh structure also provides a buffer for the expansion effect of the natural graphite negative electrode material during the cycle, thereby improving the cycle performance.

[0066] Compared with the graphite composite negative electrode material provided in Example 1, the polyhydroxybenzene in the mesh conductive layer coating of Comparative Example 3 is replaced with a long-chain 10-hydroxystearic acid, which has a different structure from the polyhydroxybenzene of the present invention, a monomer carbon number of 18, and a carbon-hydrogen ratio of 1:2, and does not belong to the scope of the present invention. Because the outer coating structure is the same as that of Example 1, the specific surface area is only slightly improved compared with Comparative Example 2, and the first efficiency is also slightly reduced. The internal resistance and rate performance are almost not improved, indicating that the conductive properties of the negative electrode material have not changed. It is speculated that this is because the 10-hydroxystearic acid molecule has fewer hydroxyl groups, which can provide fewer active sites for linking with the graphite surface and metal ions, and does not combine with enough metal ions in the coating layer. At the same time, from Figure 8 It can be seen that the thickness of the inner mesh coating structure is 2 to 3 times that of the surface soft carbon coating, the color is uneven, the internal pores are unevenly distributed, and a good mesh structure is not formed. The 1C / 1C 500-week capacity retention rate of the negative electrode material is significantly reduced by 8.2% compared with Comparative Example 2. It can be seen from the cycle curve that the cycle capacity is high in the first 250 weeks, and then drops rapidly. It is speculated that although the 10-hydroxystearic acid of the unsaturated long-chain hydrocarbon is coated on the surface of natural graphite, the fragile carbon-carbon single bond and the inappropriate carbon-hydrogen ratio cause the mesh conductive layer to boil and dissipate rapidly during the carbonization process, forming a coating layer with larger pores, uneven structure and lower strength. At the beginning of the cycle, lithium ions provide additional capacity for the negative electrode material due to the adsorption of the high-void conductive layer, but as the cycle progresses, the graphite begins to show obvious volume expansion, and the internal stress generated causes the mesh conductive layer to collapse rapidly. The structure can no longer be maintained, resulting in a rapid decrease in the cycle capacity.

[0067] Compared with the graphite composite negative electrode material provided in Example 1, the amount of polyhydroxybenzene and metal salt added in the mesh conductive layer coating of Comparative Example 4 is increased, exceeding the scope of the present invention. Because the outer coating structure is the same as that of Example 1, the specific surface area is slightly increased, the first efficiency is slightly decreased, the internal resistance is slightly increased, and the 1C capacity retention rate is 2% lower than that of Example 1, and the 3C / 5C capacity retention rate is similar to that of Example 1. The difference is that the 1C / 1C 500-week capacity retention rate of the negative electrode material is 0.7% lower than that of Comparative Example 2, which is far from the level of Example 1, indicating that when the mesh conductive layer is too thick, it is easy to cause a loose and fragile structure, and it cannot provide help for improving the cycle performance of the graphite composite negative electrode material.

[0068] Compared with the graphite composite negative electrode material provided in Example 1, the amount of polyhydroxybenzene and metal salt added in the conductive layer coating of Comparative Example 5 is reduced and is below the scope of the present invention. Similarly, because the outer coating structure is the same as that of Example 1, the first effect and the specific table are also similar. The difference is that because the coating layer is thin and sparse, the conductive particles are also sparsely distributed in the coating layer, and a good conductive path cannot be formed, especially a large number of electrons cannot be carried through quickly, resulting in the 1C / 3C / 5C capacity retention rate of the negative electrode material not being significantly improved, and a small amount of polyhydroxybenzene does not form a good network structure, and the 1C / 1C 500-week capacity retention rate is not significantly improved, and the cycle performance is almost not improved.

[0069] In Examples 4-6 of the present invention, a more reasonable proportion of polyhydroxybenzene, metal salt and surface soft carbon coating is used to obtain negative electrode material products with better first efficiency, rate performance and cycle performance, lower impedance and specific surface area, and Example 6 obtains a better product by increasing the carbonization temperature. It can be proved that the present invention can produce natural graphite composite negative electrode materials with different performances, and negative electrode products with different performances and production costs can be selected according to customer customization requirements.

[0070] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A graphite composite negative electrode material, characterized in that: The graphite composite negative electrode material has a core-shell structure, which includes a graphite core, a mesh conductive intermediate layer and a surface soft carbon coating layer; wherein the raw materials of the mesh conductive intermediate layer include polyhydroxybenzene and metal salt, the raw materials of the graphite core include natural graphite, and the raw materials of the surface soft carbon coating layer include high-temperature coated asphalt; the mass ratio of the natural graphite: polyhydroxybenzene: metal salt: high-temperature coated asphalt is 1000: 20-80: 20-80: 20-60.

2. The graphite composite negative electrode material according to claim 1, characterized in that: The mass ratio of the natural graphite: polyhydroxybenzene: metal salt: high temperature coated asphalt is 1000:40-60:50-70:45-60.

3. The graphite composite negative electrode material according to claim 1, characterized in that: The monomer carbon number of the polyhydroxybenzene is 6-15, and the carbon-hydrogen ratio is 1-1.

2.

4. The graphite composite negative electrode material according to claim 1, characterized in that: The polyhydroxybenzene includes hexahydroxybenzene and / or 3,3',4,4',5,5'-hexahydroxybiphenyl.

5. The graphite composite negative electrode material according to claim 1, characterized in that: The metal salt includes one or a combination of two or more of copper acetate, cobalt acetate and zinc acetate.

6. The graphite composite negative electrode material according to claim 1, characterized in that: The high temperature coated asphalt has a softening point of 250-300°C and a coking value of ≥70%.

7. The graphite composite negative electrode material according to claim 1, characterized in that: The quinoline insoluble matter content in the high-temperature coated asphalt is ≤0.3wt%, and the ash content is ≤0.1wt%; the median particle size D50 of the high-temperature coated asphalt is 1-6μm.

8. The graphite composite negative electrode material according to claim 1, characterized in that: The natural graphite is spherical graphite, with a median particle size D50 of 16-18 μm and a fixed carbon content of ≥99.95 wt%.

9. The graphite composite negative electrode material according to claim 1, characterized in that: The tap density of the natural graphite is ≥0.96 g / cm 3 ; The specific surface area of ​​the natural graphite is ≤6.5 cm 2 / g.

10. A method for preparing the graphite composite negative electrode material according to any one of claims 1 to 9, characterized in that: The preparation method of the graphite composite negative electrode material comprises: (1) Using surfactants to modify the surface of natural graphite to obtain surface-modified graphite; (2) mixing the surface-modified graphite and polyhydroxybenzene in water, then adding a metal salt to carry out a hydrothermal reaction, and carbonizing the product after the reaction is completed to obtain an intermediate product; (3) The intermediate product is mixed evenly with high-temperature coated asphalt, and then carbonized again to obtain the graphite composite negative electrode material.

11. The method for preparing a graphite composite negative electrode material according to claim 10, characterized in that: In step (1), the method for surface modifying natural graphite using a surfactant is as follows: uniformly mixing the surfactant with water, slowly adding graphite under stirring, heating and stirring, filtering, and drying to obtain the surface-modified graphite.

12. The method for preparing a graphite composite negative electrode material according to claim 11, characterized in that: The surfactant includes sodium dodecylbenzene sulfonate and / or hexadecyltrimethylammonium bromide.

13. The method for preparing a graphite composite negative electrode material according to claim 11, characterized in that: The mass ratio of the surfactant to the natural graphite is 1-10:1000.

14. The method for preparing a graphite composite negative electrode material according to claim 11, characterized in that: The mass ratio of water to natural graphite is 5-15:

1.

15. The method for preparing a graphite composite negative electrode material according to claim 10, characterized in that: In step (2), the temperature of the hydrothermal reaction is 70-95°C and the time is 20-120 min.

16. The method for preparing a graphite composite negative electrode material according to claim 10, characterized in that: The mass ratio of water to the surface modified graphite is 15-30:

1.

17. The method for preparing a graphite composite negative electrode material according to claim 10, characterized in that: In step (2), the carbonization method is: heating to 750-950°C at a heating rate of 1-10°C / min and keeping the temperature for 1-4h.

18. The method for preparing a graphite composite negative electrode material according to claim 10, characterized in that: In step (3), the method of re-carbonization is: heating to 1100-1350°C at a heating rate of 1-10°C / min and keeping the temperature for 1-6h.

19. A lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery is prepared from the graphite composite negative electrode material described in any one of claims 1 to 9 or the graphite composite negative electrode material prepared by the method for preparing the graphite composite negative electrode material described in any one of claims 10 to 18.

Citation Information

Patent Citations

  • A long-cycle negative electrode material and its preparation method

    CN113991076B

  • Synthesis method of conductive metal organic framework material applied to zinc ion battery

    CN113698619A

  • Negative electrode material for sodium secondary battery, electrode for sodium secondary battery, and sodium secondary battery

    JP2013168241A

  • Composite graphite particle, and its application to lithium ion secondary battery

    JP2013216563A

Cited By

  • Graphite composite negative electrode material and preparation method therefor, and lithium-ion battery

    WO2026130172A1